Excess River Sedimentation at Bridges in the Raya Graben (Northern Ethiopia). (29th July 2016) - Demissie, Biadgilgn; Billi, Paolo; Frankl, Amaury; Haile, Mitiku; Nyssen, Jan
Abstract: This study investigates the temporal variability and effects of bio‐climatic factors and bridges on local hydro‐geomorphic conditions that cause excess sedimentation and flood hazard in ephemeral rivers of the Raya graben (northern Ethiopia). Normalized difference vegetation index (NDVI) was analyzed using Landsat imageries of 1972, 1986, 2000, 2005, 2010, and 2014. Daily rainfall data of three meteorological stations were considered to analyze the temporal trends and return time intervals of rainfall intensity in 24 h. Stream‐bed gradient and bed material grain size were measured in 20 river reaches. Results show that the maximum NDVI values were recorded in the time interval from 2000 to 2014. Nevertheless, during this decade, the study bridges experienced the largest excess sedimentation, in some bridges up to 1·6 m. Different factors to account for it are discussed as no evidence of rainfall pattern, accountable for an increase in sediment delivery from the headwaters, is found. The field data show that channel narrowing at bridges is the main cause of thick upstream sedimentation and of increasing frequency of overbank flows during the last 15 years. A simple hydraulic approach is presented to explain the variability of sediment deposition at bridges and change in bed material grain size between the main stem and the reach right upstream of the bridge. Copyright © 2016 John Wiley & Sons, Ltd.